The Impact of Immunonutritional and Physical Status on Surgical Outcome After Pancreaticoduodenectomy in Elderly Patients - SUGIMACHI, KEISHI; IGUCHI, TOMOHIRO; MANO, YOHEI; NISHIJIMA, TOMOHIRO; NAKANOKO, TOMONORI; UEHARA, HIDEO; SUGIYAMA, MASAHIKO; OHTA, MITSUHIKO; IKEBE, MASAHIKO; MORITA, MASARU; TOH, YASUSHI (Anticancer research, 2019)
Background/Aim: The aim of this study was to determine the significance of immunonutritional and physical index in the assessment of risk associated with pancreaticoduodenectomy (PD) in the elderly. Patients and Methods: This study enrolled 92 patients who underwent PD. They were divided into 2 groups: Group A included patients 79 years and younger (n=79) and Group B patients 80 years and older (n=13). Among 37 patients, physical function and body composition were also evaluated. Results: Significantly higher neutrophil–lymphocyte ratio, lower prognostic nutritional index (PNI), and controlling nutritional score were observed in Group B. Muscle strength and walking ability were significantly impaired in Group B, although there was no significant difference in body composition. Age was not correlated with the incidence of postoperative complications, overall survival or recurrence-free survival by univariate and multivariate analysis. Conclusion: PD is justified for the elderly, with acceptable morbidity and prognosis. However, immunonutritional status and physical function are significantly impaired; thus, appropriate case selection and active nutritional support are required for the elderly.